Influence Organizational Culture And Work Motivation On Organizational Commitment Through Job Satisfaction - Ahmad Rasyiddin; Febri Sari Siahaan (Journal of Management and Business Innovations, 2022)
Organizational commitment was an important variable in measuring how engaged employees are. This study aims to analyze how organizational commitment is formed by organizational culture and work motivation with intervention variable which is job satisfaction. The population of this study were employees of the production division of PT. Primayudha Mandiri Jaya, with sample size was 100 respondents. This study used explanatory research where interpretation about the path of constructed model with questionnaire as techniques to collect data (Likert scale). This study used quantitative descriptive statistics as an analysis technique. Summary result indicated all variables had significant effect on organizational commitment. Organizational culture and work motivation also affected job satisfaction, but job satisfaction does not change the influence of organizational culture and work motivation on office organizational commitment.Keywords: Organizational commitment, organizational culture, job satisfaction, work motivation